Feasibility and ethical issues: experiences and concerns of healthcare workers regarding a new RSV prophylaxis programme in Nunavik, Quebec. Issue 1 (1st January 2020) - Lorcy, Armelle; Gilca, Rodica; Dubé, Eve; Rochette, Marie; De Serres, Gaston
ABSTRACT: Background : The respiratory syncytial virus (RSV) is a major cause of hospitalisation in young Inuit children. Prophylaxis with palivizumab is routinely recommended for premature infants and those with severe pulmonary or cardiac diseases. In the fall 2016, the Quebec Ministry of Health expanded the criteria to include healthy full-term (HFT) newborns from Nunavik based on their high RSV hospitalisation rates. Objectives : The aim of this study was to describe the impact of this programme on Nunavik health services during the first RSV season after its implementation (2016–2017) by studying challenges, concerns and needs of healthcare workers (HCWs). Methods : An ethnographic approach was used. Semi-structured interviews focusing on HCWs experiences, and opinions to improve the new programme were conducted with 20 HCWs involved in its implementation. Results : Main reported challenges and concerns were: additional work(over)load, lack of information and evidence about the need and efficacy of palivizumab in HFT newborns, communication issues between stakeholders, and ethical issues regarding the Inuit population. Conclusion : The study revealed significant feasibility and acceptability issues. The programme was highly resource consuming. To address HCWs' concerns, evidence-based data regarding palivizumab effectiveness in HFT infants, as well as consultation and involvement of Inuit population are warranted.